TATKELOLA SISTEM INFORMASI MANAJEMAN SEKOLAH DENGAN MODEL ENTERPRISE ARCHITECTURE PLANNING (STUDI KASUS: MA HIDAYATUL MUBTADIIN JATI AGUNG LAMPUNG SELATAN) - Saputra, Andika (STIT AL MULTAZAM, 2023)
Technological developments that continue to increase require the education system to continue to innovate. In addition to technology that continues to develop, the increasing need for technology-based academic services has become a special need for an educational institution to be able to continue to compete with strategic planning and the use of information systems. The current information system development at MA Hidayatul Mubtadiin is still carried out conventionally, that is, all administrative processes are still managed with simple applications such as word and excel. This research was carried out by building an enterprise architecture model that later could be implemented by MA Hidayatul Mubtadiin to achieve an integrated information system strategic planning so that it could be aligned with the agency's vision and mission goals. To carry out the development of enterprise architecture modeling, a complete and easy-to-use methodology is needed and one of the methodologies is EAP (Enterprise Architecture Planning) which is a detailed, complete and easy methodology for use in various organizations. Governance of this school information system can make it easier for students, teachers and prospective new students who previously did not know school information, design information systems, teachers and schools with an academic information system (online), so that it can be effective and efficient.